Pengembangan Instrumen Tes Four-Tier Multiple Choice (4TMC) Berbasis Higher Order Thinking Skill (HOTS) Materi Unsur, Senyawa dan Campuran: Pengembangan Instrumen Tes Four-Tier Multiple Choice (4TMC) Berbasis Higher Order Thinking Skill (HOTS) Materi Unsur, Senyawa dan Campuran - Saputra, Berliana Wanodya Diva; Biru, Lulu Tunjung; Islami, R. Ahmad Zaky El (UNIB Press, 2025)
It is known that some schools in Serang City are still not optimal in empowering students' Higher Order Thinking Skill (HOTS) habits and tend to lead to the C1 - C3 cognitive domain. The purpose of this study was to describe the level of validity and analyze students' responses to the Higher Order Thinking Skill (HOTS)-based Four-Tier Multiple Choice (4TMC) on Elements, Compounds, and Mixtures material in class VIII junior high school students (Phase D). Research and development was conducted using the R n D (Research and Development) method. The research was conducted using the ADDIE model which refers to the Analysis, Design, Development, Implementation, and Evaluation stages. The instruments used are interview instruments, validation questionnaires and learner response questionnaires. The subjects in this study were 3 expert lecturers of Science Education and 60 junior high school students in grade VIII. The validity level of the HOTS-based test instrument reached a value of 93.20% with the category “Very Feasible” and obtained the results of students' responses with the category “Good” at a percentage of 79.98%. Therefore, the HOTS-based 4TMC test instrument is very feasible to be used by teachers as a reference for conducting tests on science materials, especially elements, compounds, and mixtures.